2018
DOI: 10.31024/ajpp.2018.4.6.26
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective effect of aqueous extracts of root and peel of Punica granatum in wistar rats

Abstract: Objective: To evaluate the hepatoprotective effect of aqueous extracts of root (RAE) and peel (PAE) of Punica granatum. This study was conducted on adult albino Wistar rats of either sex weighing 150-Materials and Methods: 200 g. Animals were divided into five groups (n=5). Liver injury was produced by carbon tetrachloride (CCl) 1 ml/kg 4 dissolved in olive oil (1:1) given intraperitoneally on day 1 and day 4 of the study duration of 14 days. Silymarin (50 mg/kg/d) orally was used as standard drug. Test groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Hepatic protective effect of PP against hepatotoxic conditions were available in literature. [21] Aqueous extracts of root and peel of PG were reported by Khan et al [22] to have hepatoprotective effect against carbon tetracholoride induced toxicity in Wistar rats. Similar effect against carbon tetrachloride toxicity by PG seed oil was also reported by Gram et al [23] Amiri et al [24] found that administration of PG leaf extract prevents fatty changes in liver of rat receiving high fat diet.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatic protective effect of PP against hepatotoxic conditions were available in literature. [21] Aqueous extracts of root and peel of PG were reported by Khan et al [22] to have hepatoprotective effect against carbon tetracholoride induced toxicity in Wistar rats. Similar effect against carbon tetrachloride toxicity by PG seed oil was also reported by Gram et al [23] Amiri et al [24] found that administration of PG leaf extract prevents fatty changes in liver of rat receiving high fat diet.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the hepatoprotective function of PPE could be due to its phenolic compounds (Faddladdeen and Ojaimi, 2019) and enhancement of enzymatic and nonenzymatic activities (Zhai et al, 2018). According to Khan et al (2018), PPE has hepatoprotective properties against the toxic effects of carbon tetrachloride in mice liver.…”
Section: Discussionmentioning
confidence: 99%